FORMULATION EFFERVESCENT TABLETS ETHANOL EXTRACT OF PAPAYA LEAVES (Carica papaya L.) AS TOPICAL ANTISEPTIC WITH CITRIC ACID-TARTARIC ACID VARIATIONS - Partama, Tri Isa; Kristiani, Ni Kadek Ari; Priastari, Anak Agung Istri Manik; Prasetia, Gusti Ngurah Jemmy Anton (Journal Pharmaceutical Science and Application, 2022)
Background: Antiseptic products that are widely found in the market contain chloroxylenol which can cause irritation and allergic reactions when used frequently. In addition, antiseptic products in liquid form are considered less practical and economical. The alternative used to overcome these problems is to utilize natural ingredients that are made in solid dosage forms in the form of effervescent tablets. One alternative plant that has the potential as an antiseptic is papaya leaves. Objective : To determine the effect of variations in citric acid and tartaric acid as a source of acid in the formulation of effervescent tablets and to find out what formula is the effervescent tablet of papaya leaf ethanol extract has the best physical properties to meet the physical qualification requirements of the tablet. Methods: Extraction was carried out by the maceration method with 96% ethanol as solvent. The method used for the manufacture of effervescent tablets is wet granulation. Therefore, in this study, observations were made on the effect of variations in citric acid and tartaric acid (1:3; 1:1 and 3:1) on the physical quality and antibacterial activity of effervescent tablets. Result: The tablet formulations F1 with variation citric acid-tartaric acid (1:3) showed physical characteristics that met the tablet quality requirements. Based on the antibacterial activity test of Escherichia coli on effervescent tablets, papaya leaf ethanol extract (Carica papaya L.) for formulation I showed an inhibitory power of 7,5±1,29 mm. The inhibitory power is more effective than the positive control, namely antiseptic products on the market with an inhibition zone of 6,5 ± 0,05 mm. Conclusion: Based on the variation of citric acid and tartaric acid used, it did not affect the physical properties of effervescent tablets of papaya leaf ethanol extract (Carica papaya L.) including uniformity of weight, but influenced hardness, friability, and dissolving time of effervescent tablets of papaya leaf ethanol extract (Carica papaya L.). Keywords: Papaya leaf (Carica papaya L.), effervescent tablet, citric acid, tartaric acid, antiseptic